Simplifying
4(-8x + 5) = -32x + -26
Reorder the terms:
4(5 + -8x) = -32x + -26
(5 * 4 + -8x * 4) = -32x + -26
(20 + -32x) = -32x + -26
Reorder the terms:
20 + -32x = -26 + -32x
Add '32x' to each side of the equation.
20 + -32x + 32x = -26 + -32x + 32x
Combine like terms: -32x + 32x = 0
20 + 0 = -26 + -32x + 32x
20 = -26 + -32x + 32x
Combine like terms: -32x + 32x = 0
20 = -26 + 0
20 = -26
Solving
20 = -26
Couldn't find a variable to solve for.
This equation is invalid, the left and right sides are not equal, therefore there is no solution.